Elastic-Plastic Fracture 1979
DOI: 10.1520/stp35835s
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Estimation Procedures Used in J-lntegral Testing

Abstract: Estimation techniques for the calculation of J have enabled the development of simpler data reduction methods for multiple specimen J-integral tests and also prompted the development of single-specimen tests. This report describes an experimental program conducted to evaluate the accuracy of these estimation techniques. Comparisons between the values of J as calculated by the energy rate definition and those calculated by the estimation techniques for compact toughness, three-point bend, and center-cracked ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

1981
1981
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 2 publications
0
21
0
Order By: Relevance
“…Landes et al [102] showed that Eq. (18) was applicable with reasonable accuracy to ASTM E399 three-point bend and compact specimens with deep cracks, even when the load-line displacement (LLD) was substituted for the actual load-point displacement for the evaluation of A tot .…”
Section: Early J Estimation and G-factor Equationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Landes et al [102] showed that Eq. (18) was applicable with reasonable accuracy to ASTM E399 three-point bend and compact specimens with deep cracks, even when the load-line displacement (LLD) was substituted for the actual load-point displacement for the evaluation of A tot .…”
Section: Early J Estimation and G-factor Equationsmentioning
confidence: 99%
“…Since Eq. (21) is complicated in practical application, Landes et al [102] simplified this Merkle-Corten equation in terms of the total displacement as:…”
Section: Early J Estimation and G-factor Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Landes and his colleagues ( [18] and [1]) conducted many experiments of large crack extension to determine J-values and the sensitivity of fracture toughness measurements 'to both specimen geometry and different types of specimen loading. Some of their tests were run up to the maximum loads and some have load versus displacement records like the one shown in Figure 1.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[ 1 1 When conducting crack growth rate tests on a material behaving in a nonlinearly elastic manner, the methods employed to collect the raw test data become even more tedious and complex since parameters other than crack length and elapsed cycles must be measured and recorded. Crack tip opening displacement (CTOD), [21 crack tip opening angle (CTOA), [3] and the area under load vexsus displacement curves [4 ] represent a few examples of data which are collected and analyzed by investigators to obtain nonlinear fracture parameters. The determination of these parameters are again often subject to operator bias and error, besides demanding constant personal supervision.…”
Section: Introductionmentioning
confidence: 99%